2017
DOI: 10.1038/s41598-017-01903-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interference and heteroaromaticity of para- and meta-linked bridged biphenyl units in single molecular conductance measurements

Abstract: Is there a correlation between the (hetero)aromaticity of the core of a molecule and its conductance in a single molecular junction? To address this question, which is of fundamental interest in molecular electronics, oligo(arylene-ethynylene) (OAE) molecular wires have been synthesized with core units comprising dibenzothiophene, carbazole, dibenzofuran and fluorene. The biphenyl core has been studied for comparison. Two isomeric series have been obtained with 4-ethynylpyridine units linked to the core either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 49 publications
7
71
0
Order By: Relevance
“…When the electron pathway passes directly through the antiaromatic core unit, the conductance of the 2,7-disubstituted biphenylene derivative 2 is 32 times lower than that of 1, which agrees with its fluorene analogue in a previous report. 32 Molecule 3 with SMe anchoring groups shows a slightly higher conductance value (10 −4.4±0.52 G 0 ) than that of its pyridyl analogue 1 and agrees well with 1,4-bis( p-methylthiophenylethynyl) Fig. 2 Typical conductance traces for compounds 1-4 (a) and 5-8 (b), respectively.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…When the electron pathway passes directly through the antiaromatic core unit, the conductance of the 2,7-disubstituted biphenylene derivative 2 is 32 times lower than that of 1, which agrees with its fluorene analogue in a previous report. 32 Molecule 3 with SMe anchoring groups shows a slightly higher conductance value (10 −4.4±0.52 G 0 ) than that of its pyridyl analogue 1 and agrees well with 1,4-bis( p-methylthiophenylethynyl) Fig. 2 Typical conductance traces for compounds 1-4 (a) and 5-8 (b), respectively.…”
Section: Resultssupporting
confidence: 69%
“…30 In contrast, a study on a comparable series of 2,5-disubstitutedfuran, -pyrrole, -thiophene and -cyclopentadiene derivatives with pyridyl anchors found no statistically significant dependence of the conductance on the aromaticity of the core. 31 For molecules with tricyclic cores, it has been shown that increasing aromaticity at the core decreases the conductance for the para-linked molecules (dibenzothiophene < carbazole < dibenzofuran < fluorene) with pyridyl anchors, 32 in agreement with Venkatarman et al 30 However, the sequence is different for the isomers where the tricyclic core is meta-linked into the backbone (dibenzothiophene ≈ dibenzofuran < carbazole ≈ fluorene). 32 It is therefore of particular interest to explore the effect of incorporating 4n π-electron antiaromatic rings into the backbone of molecules that are wired into junctions.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Recently it has been demonstrated both experimentally and theoretically that single molecules can display bi-thermoelectric behaviour, in which the sign of S changes in response to both geometric changes [10][11][12] and the application of pressure, 11 which shi the positions of the HOMO and LUMO transport resonances relative to E F . An alternative approach to the control of quantum transport through single molecules involves utilizing quantum interference (QI) of de Broglie waves associated with electrons passing through the molecule, [13][14][15][16][17][18][19][20][21][22][23][24][25] which can increase or decrease the electrical conductance depending on whether QI is constructive or destructive. One type of molecular junction that has shown QI involves two pi-stacked molecules, [26][27][28][29][30] as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…One can tailor the properties of a device by modifying a small portion of the building unit. The backbone of the molecule will ultimately determine the specific function of the molecular device (McCreery, 2004;Michoff et al, 2013;Low et al, 2015;Xiang et al, 2016;Gantenbein et al, 2017;Bâ ldea, 2019;Lenfant et al, 2017). The molecular structure of biphenyl and its derivatives has been the subject of numerous studies.…”
Section: Introductionmentioning
confidence: 99%